The Proxima Centauri Campaign—First Constraints on Millimeter Flare Rates from ALMA - Burton, Kiana; MacGregor, Meredith A.; Osten, Rachel A.; Howard, Ward S.; Weinberger, Alycia J.; Shkolnik, Evgenya; Wilner, David J.; Forbrich, Jan; Barclay, Thomas (The Astrophysical journal, 2025)
Proxima Centauri (Cen) has been the subject of many flaring studies due to its proximity and potential to host habitable planets. The discovery of millimeter flares from this M dwarf with Atacama Large Millimeter/submillimeter Array (ALMA) has opened a new window into the flaring process and the space-weather environments of exoplanets like Proxima b. Using a total of ~50 hr of ALMA observations of Proxima Cen at 1.3 mm (233 GHz), we add a new piece to the stellar flaring picture and report the first cumulative flare frequency distribution (FFD) at millimeter wavelengths of any M dwarf. We detect 463 flares ranging from energies 10 24 to 10 27 erg. The brightest and most energetic flare in our sample reached a flux density of 119 ± 7 mJy, increasing by a factor of 1000× the quiescent flux, and reaching an energy of 10 27 erg in the ALMA bandpass, with t 1/2 ≈ 16 s. From a log–log linear regression fit to the FFD, we obtain a power-law index of α FFD = 2.92 ± 0.02, much steeper than α FFD values (~2) observed at X-ray to optical wavelengths. If millimeter flare rates are predictive of flare rates at extreme-UV wavelengths, the contribution of small flares to the radiation environment of Proxima b may be much higher than expected based on the shallower power-law slopes observed at optical wavelengths.